74 a musical play / book - Edwards, Sherman. 4 0 16; 1930-2003. Stone, Peter; 5 (New York : Penguin Books, 1970)
Presents the script for the Tony Award-winning musical play which follows the events of the Second Continental Congress, from May 8 to July 4, 1776, leading up to the signing of the Declaration of Independence.
Reprint of the ed. published by The Viking Press, New York.
Includes bibliographical references (p. [174]-176).
Adult;Adult
Keywords: 2 -- 0; 6; Librettos. -- Musicals;Librettos.;Musicals librettos; 20; 2